Comparative Study of Open Source Network Security Tools: Nmap and New Candidates in Network Scanning - Barros, Laura Carvalho de; Denarde, Gabriel; Pasa, Guilherme de Mello; Salvador, Pedro Henrique; Priesnitz Filho, Walter (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2025: Anais do XXII Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2025.16555, 2025)
This article analyzes the benefits and limitations of using alternative tools to Nmap in network scanning and vulnerability detection activities. While Nmap is widely recognized for its depth of analysis, versatility, and scripting support, tools like Masscan, ZMap, RustScan, Angry IP Scanner, and OpenVAS offer specific advantages such as increased speed, simplicity, or a focus on automated tasks. However, these alternatives may sacrifice accuracy, detail, or flexibility. The choice between them depends on the necessary balance between speed, depth, and context of the application. In conclusion, using multiple tools together works best. Fast tools like Masscan and ZMap are good for the first scan. Nmap or RustScan can then give more details. And OpenVAS should be used for in-depth security checks.